Kajian prestasi dan emisi enjin terhadap kesan asid oliek teroksida sebagai bahan tambah bahan api petrol - Yusoff Ali,; Abdul Amir Hassan Kadhum,; Irfan Wahyudi, (2010)
The objective of this study is to investigate the effect of oxygenated oleic acid additives in standard petrol on the engine performance and the exhaust emissions. The 4-stroke 1.5 litre engine was used on the engine test bed coupled to eddy current electric dynamometer which is also connected to CADET V12 control system and exhaust gas analyser IMR 2000/2000P. The oxygenated oleic acid additives used for this experiment is fixed at 0.2% by volume due to limited quantity available. Two types of test were carried out first test is with variable speed and no loads and the second test is at constant speed of 1,400 rpm with variable loads. The experimental results showed that the brake power increased by 2%, torque by 2%, brake thermal efficiency by about 7% and specific fuel consumption decreased by about 10%. The exhaust emissions analysed are carbon monoxide, (CO), carbon dioxide (CO2) and oxides of nitrogen (NOx). The result by comparing the oxygenated petrol with the standard petrol indicated that CO gas emission depend on the engine speed which decreased with increasing speed up to 1,600 rpm and increased after that speed on test without load. The CO also decreased by about 28% on the test with loads. The emission of CO2 increased by 2.7% for tests with load and by 8% for tests without loads. The NOx emission decreased by 9% for test without load and about 7% for test with load. This study indicates that engine performance is improved by adding 0.2% oxygenated additives to standard petrol